EFEKTIVITAS REBUSAN KAYU MANIS DAN DAUN KERSEN TERHADAP PENURUNAN KADAR GULA DARAH - Awaluddin, Awaluddin; Nurfariza, Vera (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract : Diabetes mellitus (DM) is still a major global health problem. This disease, commonly called sugar disease or diabetes, causes the sufferer's body to be unable to regulate blood glucose levels. One non-pharmacological therapy that can reduce blood sugar levels is cinnamon. Apart from cinnamon, cherry leaves can also lower blood sugar. The purpose of this study is to determine the effectiveness of cinnamon decoction and cherry leaves on reducing blood sugar levels in patients with type II diabetes mellitus. This quasi-experimental design is of the